Nanoparticle heterojunctions in ZnS/ZnO hybrid nanowires for visible-light-driven photocatalytic hydrogen generation - Wang, Zheng (2013)
We report one-step hydrothermal preparation of ZnS/ZnO hybrid nanowires consisting of well-distributed nanoparticle-heterojunctions that induce high activity for visible-light-driven H2 evolution even without any noble metal co-catalysts. During the growth process, the nanoparticulated ZnS nanowires formed first, followed by ZnO nanocrystal growth with intercalation inside the ZnS nanowires. This growth mode 10 could result in enriched ZnS-surface-states on the ZnO nanocrystal surfaces, as evidenced by the weakened absorption features and quenched band gap emission of ZnO in the ZnS/ZnO hybrid nanowires. Further studies by varying the ZnS to ZnO ratio in the ZnS/ZnO hybrids also proved that the population of ZnS-surface-states is crucial to the visible-light activity for photocatalytic H2 evolution. This work provides a meaningful way to develop heterostructured composites as visible-light-active photocatalysts 15 by using wide band gap semiconductors for solar fuels production.